PENGEMBANGAN MEDIA GAME PEMBELAJARAN IPAS MATERI TRANSFORMASI ENERGI DISEKITAR KITA MENGGUNAKAN APLIKASI WORDWALL KELAS IV SDN 108/VIII SARI MULYA - Muhammad Subhan; Ratnawati; Ervi Wulan Suci (STKIP Subang, 2023)
This research is motivated by the lack of use of interesting learning media to support the learning process, especially in class IV A SD N 108/VIII Sari Mulya. So, it takes effort to develop learning media. This study aims to produce learning media that have valid, practical and effective criteria. This research is a development research. The model used for this development is the ADDIE development model. The ADDIE development stages consist of: Analysis Stage, Design Stage, Development Stage, Implementation Stage, and Evaluation Stage. The results of the learning game media validation research were carried out by three validators, namely: validator I was 83.33%, validator II was 83.33%, and validator III was 100% which had an average value of 88.88% with a very valid category seen from the suitability of language, content and media graphics. The results of the practicality assessment of the learning game media were carried out by two practitioners, namely: practitioner I was 75% and practitioner II was 100%, which had an average of 88% in the very practical category. The results of the effectiveness of the learning game media obtained from the response questionnaire of class IV A students at SD N 108/VIII Sari Mulya have a value of 94% with a very effective category. The results of the study can be concluded that the development of learning game media has valid, practical and effective criteria.